Penerapan Etika Bisnis Terhadap Kepuasan Konsumen dalam pandangan Islam - Ahmad Syafiq (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2019)
Abstract Increased economic growth has led to higher public incomes and ultimately has been the driver of growth in household consumption. So that causes public consumption of goods and services also increases. Given the high level of consumption, and in order to increase corporate income, and increase customer satisfaction, Business Ethics plays a very important role. Profit is not the only object sought by business people. Besides profits, business people need to realize customer satisfaction. Where consumer satisfaction is also one indicator measuring how much the company cares about consumers, so it does not lead to the notion that the company is selfish, and only has the purpose of making profits without thinking about consumer welfare and satisfaction. Islam teaches that we be fair, and are mutually beneficial (help). Therefore, we are encouraged to have an attitude and ethics in doing business, so that not only we feel profitable, but also the consumers. So that after consuming our products, the consumer feels that the products and prices we make and distribute are balanced with the quality and function of the product.